Drug Utilization Study of Vancomycin in a Tertiary Hospital - Ningrum, Vitarani Dwi Ananda; Ambariyah, Nurul; Fortuna, Camelia Dewi; Yulianto, Yulianto (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Vancomycin possesses not only a narrow therapeutic range but also nephrotoxic effects, thus requiring intensive monitoring. This study aims to analyze the vancomycin use among the inpatients of a referral in Indonesia. This retrospective cross-sectional research collected a two-year data from medical records. The research involved all the patients who met the inclusion criteria. The majority of the 90 patients receiving vancomycin were men with the most age range of 18-60 years. The dominant indication of vancomycin use was sepsis typically caused by methicillin-resistant Staphylococcus aureus (MRSA) and Staphylococcus haemolyticus. Meanwhile, the vancomycin dosing for the 1-<18 age range was mostly based on actual body weight, whereas that for other age categories took into account renal function. The effectiveness of vancomycin based on White Blood Cells and neutrophils was shown in 34.88% of patients examined for both parameters. In addition, 6.25% of the patients given a platelet count experienced suspected vancomycin-induced thrombocytopenia. No incidence of vancomycin-induced neutropenia and nephrotoxicity was found. Given that the risk of nephrotoxicity and the effectiveness of vancomycin are influenced by the steady-state concentrations and the area under the curve, this study recommends hospitals in Indonesia to provide Therapeutic Drug Monitoring (TDM) services.